Clinical exome sequencing identifies novel gene variants associated with ischemic stroke in the Saudi Tabuk population - Hamadi, Abdullah; Mir, Rashid; Al-Amer, Osama M.; Alasseiri, Mohammed; AlZamzami, Waseem; Alatawi, Sael; Alanazi, Mohammad A.; Moawadh, Mamdoh S.; Oyouni, Atif Abdulwahab A.; Al Tuwaijri, Abeer; Althenayyan, Saleh; Madkhali, Hassan A.; et al. (Frontiers in Human Neuroscience, 2026)
BackgroundVariants linked to the risk of ischemic stroke have been discovered through genome-wide association studies (GWASs). These variations frequently have little consequences that lack apparent biological significance. Hence, these findings demonstrate that exome sequencing can be highly relevant to stroke, even though stroke is a complex phenotype with various diseases and risk factors.MethodologyIn this case-control investigation, we used ARMS genotyping to investigate the distribution of polymorphic variations in genes associated with stroke susceptibility. In addition to examine the novel gene variations associated with ischemic stroke we utilized the Illumina NovaSeq 6000 platform for whole-exome sequencing (WES).ResultsResults identified 11 novel gene variants in the GSTT4 gene by targeted whole-exome sequencing, including one deletion GSTT4p.Asn232LysfsTer6, one insertion c.688_689insCG, and 9 SNVs c.699 T > C, c.701C > G, c.708G > T, c.710 T > G, c.712A > G, c.712A > G, c.718A > T, c.719G > A, c.721A > T, c.722G > T in the ischemic stroke patients. We also identified several rare, intermediate, and most common gene variants in cholesterol associated genes LDLR, LDLRAD2, LDLRAD3, APOA2, APOA3, APOA4, APOA5, and PCSK9. Also, several common gene variants were reported in MTHFR, KLF14, eNOS3, and ACE by whole-exome sequencing. Furthermore, the eNOS3-GG and eNOS3-GT genotypes were associated with susceptibility to ischemic stroke (OR = 1.95, p < 0.05).ConclusionThis case-control study identified 11 novel GSTT4 variants and several known polymorphisms associated with ischemic stroke risk in Saudi patients. These findings highlight population-specific genetic factors that warrant further functional and large-scale validation.